Daya Antibakteri Minyak Atsiri Cananga odorata terhadap Pertumbuhan Bakteri Streptococcus mutans ATCC 25175 - Avelyana Amarissa Dyartha; Dian Lesmana; Philips Onggowidjaja (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Caries is a disease of dental hard tissue, which is caused by the activity of a cariogenic microorganism. Streptococcus mutans is a gram-positive, spherical, facultative anaerobic, non-motile bacterium. Streptococcus mutans acts as an agent that can cause dental caries. Herbal medicines are preferred by the community because the risk of side effects is lower than chemical drugs. The purpose of the study was to know the antibacterial property of Cananga odorata essential oil on the growth of Streptococcus mutans bacteria ATCC 25175. This study used a laboratory experimental research design with disc diffusion method to know the antibacterial property of Cananga odorata essential oil on the growth of Streptococcus mutans ATCC 25175. The results showed an inhibitory zone of 0.25 mm at a concentration of 6.25%; 1.43 mm at a concentration of 12.5%; 1.93mm at 25% concentration; 2.21 mm at 50% concentration; and 4.48 mm at a concentration of 100%. The conclusion of this study is Cananga odorata essential oil has a weak antibacterial property on the growth of Streptococcus mutans ATCC 25175.